Analysis of lactic acid bacteria species in Miang, a post-fermented tea in Thailand, and their potential use as probiotics - Horie, Masanori; Ruengsomwong, Supatjaree; Ohmiya, Yoshihiro (Frontiers in Microbiology, 2024)
Introduction: Miang is one of the post-fermented teas made in Northern Thailand. Although lactic acid bacteria are involved in fermentation of Miang, details are still not clear. This study investigated the diversity of Lactobacillaceae bacteria, related to fermentation of Miang. Probiotic potential of isolated Lactobacillaceae bacteria was examined.Methods: Lactobacillaceae bacteria were isolated from fifty-two Miang samples collected from three provinces in northern Thailand and identified by MALDI-TOF MS. Heamolytic activity, antibiotic susceptibility, antimicrobial activity and tolerance to gastrointestinal juice were examined for probiotic potential of isolates.Results: A total of 1,181 Lactobacillaceae bacteria strains were isolated from Miang. The most abundant isolates were Lactiplantibacillus pentosus. Besides Lactiplantibacillus plantarum, Levilactobacillus brevis, Paucilactobacillus suebicus, Lacticaseibacillus pantheris, and Secundilactobacillus collinoides were also found with frequency. Of these isolates, 450 with a high score for MALDI-TOF identification were then screened for probiotic ability. Most isolates were resistant to aminoglycosides and clindamycin. Then, 35 isolates were tested for their antimicrobial activity against pathogens using the well diffusion method, and 31 isolates exhibited inhibition zones against Staphylococcus aureus, Staphylococcus epidermidis, Salmonella enterica serovar Typhimurium, S. enterica serovar Enteritidis, Listeria monocytogenes, Propionibacterium acnes, and Streptococcus mutans. All 31 isolates were non-hemolytic and readily tolerated simulated gastric juice at pH 3 and simulated intestinal juice at pH 8. Discussion: Miang contains lactic acid bacteria that could potentially be used as probiotics.